Confectionery technology for patients with diabetes and celiac disease - Dorohovich, Victoriya; Lazorenko, Natalia; Mykhailova, Nelia (My University, 2013)
Summary: Celiac disease is a chronic, systematic disease characterized by mucosa damage of the small intestine by gluten, which is a component of the wheat, rye and oats gluten complex. Celiac disease is often accompanied by diabetes. At the National University of Food Technologies it is conducted the research aimed at the development of pastry (cakes, muffins, biscuits) for patients with diabetes and celiac disease.
Keywords: biscuits; celiac disease; diabetes; muffins; cakes; печиво; целіакія; діабет; кекси; тістечка; печенье; целиакия; диабет; кексы; пирожные; кафедра іноземних мов професійного спрямування; кафедра технології харчування та ресторанного бізнесу; кафедра технології хлібопекарських і кондитерських виробів